ESTIMATION OF FETAL WEIGHT: REFERENCE RANGE AT 17-25 GESTATIONAL AGE ACCORDING TO ANTHROPOMETRICAL PARAMETERS - Trpkovska, Biljana; Zafirova, Biljana (Journal of Morphological Sciences, 2022)
The screening and management of abnormal fetal growth, whether it be  macrosomia or growth restriction, remain important objectives of  prenatal care.  The measurement of fetal biometry in the second and third trimesters is an important part of these examinations and biometric measurements are combined routinely in order to calculate the estimated fetal weight (EFW) .  EFW is a useful parameter with which to predict birth weight and outcome when it is calculated a few days before delivery. Total number of fetuses (n=210) according to gestational age were divided in three groups (first group 17-19g.a; second group 20-22g.a and third group 23-25g.a). Each group was divided in subgroups according to the sex criterion. Anthropometrical parameters were measured using methodology of the International Biological Programme (IBP) with standard technique of measurement and equipment. Fetal parameters were analyzed: fetal weight (FW), fetal length (FL), biparietal diameter (BPI), head circumferences, thigh circumferences, Mid Upper arm circumferences, abdominal circumferences, longitudinal and transversal parameters. The fetal weight as a basic characteristic and indicator of the physical growth is of great practical importance because it supplies information whether the fetuses weight is normal for the gestational week or there are some deviations which lead to an abnormal development of the fetus. The results showed that anthropometrical parameters of the fetus were in positive correlations with fetal weight and their values were increased in different groups according to gestational age. Fetal anthropometric models are strongly predictive of actual fetal weight. The need for using measurements of some anthropometrical parameters of the fetus are imposed as sensitive, safe and sample, above all compelling in routine clinical practice. Key words: fetus, fetal length, fetal weight, anthropometrical parameters.